Endovascular occlusion of pial arteriovenous macrofistulae, using pCANvas1 and adenosine-induced asystole to control nBCA injection. Issue 6 (December 2017) - Lylyk, P; Chudyk, J; Bleise, C; Serna Candel, C; Aguilar Pérez, M; Henkes, H
Background: In large-caliber pial macrofistulae (pMF), the combination of high blood flow velocity and large efferent artery diameter makes control over the endovascular vessel occlusion difficult and may result in the inadvertent venous passage of occlusive devices or embolic agents. Case descriptions: Patient 1: A 27-year-old man presented with headache and ataxia. An infratentorial pMF supplied by both superior cerebellar arteries with venous ectasia was found. The first treatment attempt using balloons and coils failed since the position of either device could not be controlled because of a distal diameter of the feeding artery of 8 mm. In a second session a pCANvas1 (phenox) was deployed at the level of the arteriovenous connection and adenosine-induced asystole allowed the controlled injection of nBCA/Lipiodol with partial occlusion of the pMF. A remaining arteriovenous shunt was occluded under asystole in a third session. The procedures were well tolerated, the patient returned to normal and DSA confirmed the occlusion of the fistula. Patient 2: A 13-year-old boy with hereditary hemorrhagic teleangiectasia presented with an intracerebral hemorrhage from an aneurysm of the left MCA. Twelve weeks after the aneurysm treatment a feeding MCA branch (diameter 4.5 mm) of a right frontal pMF was catheterized. The macrofistula was occluded by deployment of a pCANvas1, followed by the injection of nBCAl/Lipiodol under adenosine-induced asystole. Conclusion: pCANvas1 and adenosine-induced asystole allow a controlled injection of nBCA/Lipiodol for the endovascular occlusion of high-flow pMF without venous passage of the embolic agent.